Isolated Bacteria from body surface and gut for (Turckestan Cockroach) Shelfordella laterlis (Walker) in Baghdad city (Journal of the College of Basic Education, 2022)
The Cockroaches is historically Known from insects and old . Species of which are currently scattered resemble fossilized assets . Description of 4000-5000 were Somewhat divided in to the 440 genera of Cockroaches Ismail ( 1) feeding on different kinds of food which made them a varirty of nutrition depending on the members of her mouth biting chewing . Given the lack of studies on this Cockroache and there is no proof its importance in medical transfer bacteria in Iraq . It has been prepared in this research .Through living in nearby places for humans to be a Candidate as a vector a mechanic bacteria . Rueger& Olson (2) . Have many kinds of bacteria by isolation Glasere (3) . Steinhaus (4) . Said Rivault et.al. (5).The possibility of a Kind bacteria isolated from the total 157 model for Cokrouches in different environment and 56 were 14 of them Causing disease in humans .